DEVELOPMENT OF TANSARAN BIDIN TOURISM VILLAGE BANDAR DISTRICT BENER MERIAH REGENCY - Muryali; Marlina; Ahmad Yani; Muhammad Hasyem; Ti Aisyah (RADJA PUBLIKA, 2026)
The development of sustainable tourism villages is a great potential in realizing prosperous and independent villages. Adequate development of tourist destinations, both in quality and quantity, both public infrastructure facilities and supporting facilities, is needed that are able to attract tourists. Improving destinations and the concept of tourism village potential needs to be developed to add value to the uniqueness of tourist attractions. To become a tourist village, it must have 3 components, namely having tourism potential, community interest and readiness for the development of local tourist destinations and the uniqueness of the concept of a tourist village. That the implementation of tourism villages has not fully implemented sustainable tourism and made culture the main capital. Therefore, it is necessary to develop and develop tourist villages towards progress and independence. The purpose of this study is to find out the development of the Tansaran Bidin Waterfall Tourism village, Banda District, Bener Meriah Regency and also to find out the factors that hinder the implementation of the development of the tourist village object. This study uses a qualitative descriptive research method with data collection techniques through observation, interviews and documentation. Based on the results of the study, it shows that the implementation of the construction of the Bidin Tansaran Waterfall tourist attraction by the Village Government with BUMK (Village-Owned Enterprises) and the community. The construction of the Bidin waterfall tourist destination is inadequate, the implementation is still at the stage of building basic (general) infrastructure facilities and is inadequate. It has not yet reached a developing status. . Facilities/infrastructure, road access/transportation to the location are still very limited, public facilities are inadequate. Parking is not yet available. Services to tourists are inadequate. Promotion is still simple, so the results have not been able to significantly increase the number of tourist visits, nor have they been able to improve the community's economy. . The quality of the concept of the development of the Bidin Tansaran Waterfall tourist destination is still limited, it does not have a sustainable development plan. The obstacles experienced in the development of the Tansaran Bidin Waterfall tourist village are budget limitations so that they have not been able to improve the quality and quantity of the development of the Tansaran Bidin Waterfall tourist destination. The limitations of the development of the regional government for village officials, Pokdarwis, BUMK and the community in building and improving the status of tourist villages, so that there is still a low level of competent and trained human resources, limitations in the development of the unique concept of tourism village progress.